2012
DOI: 10.3346/jkms.2012.27.7.772
|View full text |Cite
|
Sign up to set email alerts
|

Juxtapapillary Duodenal Diverticula Risk Development and Recurrence of Biliary Stone

Abstract: We assessed whether the presence of juxtapapillary duodenal diverticula (JPDD) risks biliary stone disease and recurrence. In total, 695 patients who underwent ERCP were divided into two groups: biliary stone disease (group I, n = 523) and non-stone biliary diseases (group II, n = 172). Additionally, for a control group (group III), 80 age-matched healthy subjects underwent side-view duodenoscopy. In group I, rates of post-ERCP pancreatitis, cannulation failure, and disease recurrence in two-year follow up wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 17 publications
3
21
0
Order By: Relevance
“…It is reported in the literature that stones in the common bile duct occur significantly more often in patients with diverticuli [12, 13], indicating that the anatomical abnormality and malfunction of the sphincter of Oddi possibly play an important role in the formation of stones [14]. Also periampullary diverticuli are associated with larger stones and severe cholangitis [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported in the literature that stones in the common bile duct occur significantly more often in patients with diverticuli [12, 13], indicating that the anatomical abnormality and malfunction of the sphincter of Oddi possibly play an important role in the formation of stones [14]. Also periampullary diverticuli are associated with larger stones and severe cholangitis [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…In the elderly, a weakened wall and increased luminal pressure may facilitate outpouching of the duodenal mucosa through the vulnerable spot. 18,19 Pathologic mechanisms through which Lemmel's syndrome is thought to occur include the following. First, diverticulitis or direct mechanical irritation of diverticulum cause distal CBD or ampulla directly compressed mechanically by PAD.…”
Section: Discussionmentioning
confidence: 99%
“…They develop extraluminal outpouching of the duodenal wall through locus minoris resistance, and their incidence increases with age 5) . Both JPDD and IPD are often complicated with hepato-biliary-pancreatic diseases because of their anatomical proximity to the papilla Vateri [1][2][3][4][5][6] . The incidence of JPDD including IPD and hepato-biliary-pancreatic diseases (i.e., liver disfunction, cholecystitis, cholelithiasis, and pancreatitis) also increases with age 5,6) .…”
Section: Introductionmentioning
confidence: 99%
“…- 731 -日本外科系連合学会誌 第 41 巻 5 号 It has been suggested that mechanical obstruction of the common bile and pancreatic ducts is caused by JPDD including IDP 6) . Moreover, Oddi dysfunction has been found in patients with JPDD and IDP [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation